Fast Chase algorithm with an application in turbo decoding - Hirst, S.A.; Honary, B.; Markarian, G. (IEEE transactions on communications, 2001)
Turbo product codes (TPCs) provide an attractive alternative to recursive systematic convolutional (RSC)-based turbo systems. Rather than employ trellis-based decoders, an algebraic decoder may be repeatedly employed in a low-complexity, soft-input/soft-output errors-and-erasures decoder such as the Chase algorithm. Taking motivation from efficient forced erasure decoders, this implementation re-orders the Chase algorithm's repeated decodings such that the inherent computational redundancy is greatly reduced without degrading performance. The result is a highly efficient fast Chase implementation. The algorithm presented here is principally applicable to single error-correcting codes although consideration is also given to the more general case. The new decoder's value in practical turbo schemes is demonstrated via application to decoding of the (64,57,4) extended Hamming TPC.